Staphylococcal Enterotoxin-Like Toxins U2 and V, Two New Staphylococcal Superantigens Arising from Recombination within the Enterotoxin Gene Cluster - Thomas, Damien Yann (American Society for Microbiology, 2006)
To test the hypothesis that the Staphylococcus aureus enterotoxin gene cluster (egc) can generate new enterotoxin genes by recombination, we analyzed the egc locus in a broad panel of 666 clinical isolates of S. aureus. egc was present in 63% of isolates, confirming its high prevalence. The archetypal organization of the egc locus, consisting of five enterotoxin genes plus two pseudogenes, was found in 409 of 421 egc-positive strains. The egc locus was incomplete in a few strains and occasionally harbored an insertion sequence and transposase genes. These strains may represent evolutionary intermediates of the egc locus. One strain with an atypical egc locus produced two new enterotoxins, designated SElV and SElU2, generated by (i) recombination between selm and sei, producing selv, and (ii) a limited deletion in the ϕent1-ϕent2 pseudogenes, producing selu2. Recombinant SElV and SElU2 had superantigen activity, as they specifically activated the T-cell families Vβ 6, Vβ 18, and Vβ 21 (SElV) and Vβ 13.2 and Vβ 14 (SElU2). Immunoscope analysis showed a Gaussian CDR3 size distribution of T-cell receptor Vβ chain junctional transcripts of expanded Vβ subsets in toxin-stimulated cultures, reflecting a high level of polyclonality. These data show that egc is indeed capable of generating new superantigen genes through recombination.